On the international spillovers of US quantitative easing - Marcel Fratzscher; Marco Lo Duca; Roland Straub (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The paper analyses the global spillovers of the Federal Reserve's unconventional monetary policy measures. First, we find that Fed measures in the early phase of the crisis (QE1), but not since 2010 (QE2), were highly effective in lowering sovereign yields and raising equity markets in the US and globally across 65 countries. Yet Fed policies functioned in a procyclical manner for capital flows to emerging markets (EMEs) and a counter-cyclical way for the US, triggering a portfolio rebalancing across countries out of EMEs into US equity and bond funds under QE1, and in the opposite direction under QE2. Second, the impact of Fed operations, such as Treasury and MBS purchases, on portfolio allocations and asset prices dwarfed those of Fed announcements, underlining the importance of the market repair and liquidity functions of Fed policies. Third, we find no evidence that FX or capital account policies helped countries shield themselves from these US policy spillovers, but rather that responses to Fed policies are related to country risk. The results thus illustrate how US unconventional measures have contributed to portfolio reallocation as well as a re-pricing of risk in global financial markets.
Keywords: E52; E58; F32; F34; G11; 330; monetary policy; quantitative easing; portfolio choice; capital flows; Federal Reserve; United States; policy responses; emerging markets; panel data